PEMBATALAN HAK MEREK YANG TELAH DIJADIKAN JAMINAN FIDUSIA - Cantika, Delila Pritaria (Jurnal Yuridis, 2018)
Trademark as a part of intellectual property rights in essence is a sign to identify and distinguishing a product that made by a company with other products in the market. Trademark must be registered to gain a legal recourse in the form of Rights Over Trademark. However a registered trademark can still be nullified, based on a certain adequate evidence the registered trademark cannot fulfilled the absolute grounds or relative grounds. In furtherance, nowadays trademark legally feasible to be registered as a collateral. And as for the most accurate form of the collateral itself according to the law shall be registered fiduciary guaranty.